Analyzing the plastid trnL-trnF sequences of Vietnamese Solanum procumbens Lour. plants - Hue, Huynh Thi Thu; Hoa, Nguyen Thi Thanh; Hien, Le Thi Thu; Ton, Nguyen Dang (Vietnam Journal of Biotechnology, 2021)
Solanum is a genus which belongs to Solanaceae family, includes many species of cropsor medicinal plants as eggplant, tomato, potato, twoleaf nightshade, etc. Number of species are used as medicinal herbs of Solanum genus in Vietnam is up to 41, one of those is Solanum procumbens Lour., which is often used to treat hepatitis or cirrhosis. The needs of planting this plant is rising up, but it still lacks of studies based on DNA barcode of Solanum, in order to prevent the confusion of the raw materials in dry form of medicinal plants. This study provides sequencing and analysis the DNA barcode region trnL-trnF, in order to support further researches about identification, classification and evolution of Solanum procumbens species. The DNA covering the trnL-trnF region was amplified, sequenced and the nucleotide sequences from 10 samples of dry leaves Solanum procumbens species were analyzed with the reference sequences from GenBank. The results show that the similarity between these samples and others in previous publications of Solanum procumbens Lour. is 100%. Moreover, the estimated genetic distance on trnL-trnF region of the Vietnamese samples compared to few other species in Solanum genera varies between 0,0082 to 0,0399. The data from this research provides more information for any further studies about genome biodiversity of the Solanum genus as well as Vietnamese medicinal plants.